A STUDY TO ASSESS THE KNOWLEDGE REGARDING THE PREVENTION OF MINOR AILMENTS DURING PREGNANCY AMONG PREGNANT WOMEN IN SELECTED HOSPITALS OF VADODARA - Ms. Nita Patel; Pandor Bharti; Bhabhor Pinky; Rathva Jasmina; Labana Kavya (The Bioscan, 2025)
Pregnancy is a critical phase during which women often experience a variety of minor ailments such as nausea, vomiting, heartburn, constipation, backache, and leg cramps. If left unaddressed, these ailments can negatively affect both maternal and fetal health. Awareness and knowledge regarding their prevention play a vital role in ensuring a safe pregnancy and improving maternal well-being. This study aimed to assess the level of knowledge regarding the prevention of minor ailments among pregnant women attending a selected hospital in Vadodara and to examine the association of knowledge with selected socio-demographic variables. A quantitative descriptive research design was adopted, and a total of 60 pregnant women were selected using a non-probability purposive sampling technique. Data were collected using a structured questionnaire that included demographic information and knowledge-related questions. Descriptive and inferential statistical methods were used for data analysis. The results revealed that 81.7% of participants had an average level of knowledge, 15% had good knowledge, and 3.3% had poor knowledge. A statistically significant association was found between educational status and the level of knowledge (p = 0.02), suggesting that women with higher educational qualifications had better awareness regarding the prevention of minor ailments during pregnancy. No significant associations were observed with other variables such as age, caste, occupation, income, type of family, or prior information. The study concludes that while most pregnant women possess basic knowledge about minor ailments, there is a need for structured antenatal education programs to enhance their understanding and promote safe motherhood. KEYWORDS: Knowledge, Minor Ailments, Prevention, Pregnant Women.